Osoby trzecie jako współczynnik efektywnej ochrony sądowej w cywilnym postępowaniu procesowym - Dróżdż, Kinga (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In the present work the author leads to demonstration that participation of third parties in civil litigation proceedings forms one of the factors that significantly influence the securing of efficient court protection. This influence in case of participation of the discussed category of subjects can be completed exclusively by providing aid to one of the parties of the proceedings. Nevertheless it can adopt a significantly more meaningful character, when the participation of third parties in proceedings leads to counteracting negative proceeding phenomena, that could lead to distortion of the whole civil law court proceedings. The subsequent fragments of work discuss the respective procedural institutions, such as e.g. secondary intervention, third party action, main intervention or action of art. 841 of the Polish Code of civil proceedings that form the tools that allow support of third person in accomplishment of the aims of civil court proceedings in the best way possible.